Algorithm to List All Possibilities of Minimizing The Number of BSO’s of Matrix Converters - Igney, Jens; Hahn, Ingo (2024 Energy Conversion Congress & Expo Europe (ECCE Europe), 2024)
As with other self-commutated inverters, the matrix converter offers the option of discontinuous modulation. This paper presents an algorithm that lists all duty cycle matrices that allow pulse patterns with only six instead of twelve branch switching operations (BSO’s) per modulation period. It further provides a classification scheme for such duty cycle matrices. The algorithm can be used as a first step within improved modulation strategies with reduced number of branch switching operation
Keywords: AC-AC power conversion; matrix converters; pulse width modulation; branch switching operation (BSO); discontinuous modulation; classification scheme